Exploratory Research Activities in Math Class - Limas Berrio, Leidy Johana; Jiménez Espinosa, Alfonso (Eco Matemático, 2017)
This review article establishes the exploratory research activities, investigation tasks and study rooms or mathematical investigations, and their characteristics, in order to begin reviewing the use of common terms in the classroom, such as exercise, problem and problem solving, precisely in order to distinguish, it is made to establish some differences from the initial activities. Moreover, it highlights the student and teacher roles in the development of such activities. The article also presents some specific mathematics research. Finally, it demonstrates an open attitude to the theme in question, whilst considering the preexisting research into exploratory research activities and its contribution to the teaching and learning process